Composite Layers “MgAl Intermetalic Layer / PVD Coating” Obtained On The AZ91D Magnesium Alloy By Different Hybrid Surface Treatment Methods - Smolik J.; Mazurkiewicz A.; Kacprzyńska-Gołacka J.; Rydzewski M.; Szota M.; Mizera J. (Archives of Metallurgy and Materials, 2015)
Magnesium alloys have very interesting physical properties which make them ‘materials of the future’ for tools and machine components in many industry areas. However, very low corrosion and tribological resistance of magnesium alloys hampers the implementation of this material in the industry. One of the methods to improve the properties of magnesium alloys is the application of the solutions of surface engineering like hybrid technologies. In this paper, the authors compare the tribological and corrosion properties of two types of “MgAlitermetalic / PVD coating” composite layers obtained by two different hybrid surface treatment technologies. In the first configuration, the “MgAlitermetalic / PVD coating” composite layer was obtained by multisource hybrid surface treatment technology combining magnetron sputtering (MS), arc evaporation (AE) and vacuum heating methods. The second type of a composite layer was prepared using a hybrid technology combined with a diffusion treatment process in Al-powder and the electron beam evaporation (EB) method. The authors conclude, that even though the application of „MgAlitermetalic / PVD coating” composite layers can be an effective solution to increase the abrasive wear resistance of magnesium alloys, it is not a good solution to increase its corrosion resistance.